Electrochemical reduction and voltammetric determination of diloxanide furoate in non-aqueous medium - Santos, André L. [UNESP]; Takeuchi, Regina M. [UNESP]; Stradiotto, Nelson Ramos [UNESP] (FapUNIFESP (SciELO), 2005)
The electrochemical reduction of diloxanide furoate (DF) in acetonitrile on glassy carbon electrode was studied in this work. It was observed that DF is reduced after a reversible one-electron transfer followed by an irreversible chemical reaction, diagnosed as C-Cl bond cleavage. Its reduction was followed by linear (LSV), differential pulse (DPV) and square wave voltammetry (SWV). Analytical curves were obtained for DF determination using all the investigated voltammetric techniques. For LSV was obtained a linear range (LR) from 5.0 × 10-4 to 1.0 × 10-2 mol L-1, with detection limit (DL) of 1.5 × 10-4 mol L-1 and sensitivity (S) of 2.1 × 104 μA mol-1 L. The analytical parameters obtained by DPV were: LR = 5.0 × 10-4 to 2.2 × 10-3 mol L-1, DL = 7.8 × 10-5 mol L-1, S = 3.7 × 104 μA mol-1 L. For SWV were obtained a LR = 7.5 × 10-6 to 1.2 × 10 -3 mol L-1, DL = 5.5 × 10-6 mol L -1 and S = 2.8 × 105 μA mol-1 L. Thus, the SWV was the most sensible technique, which can be used for DF determination at low concentration levels. Statistics methods were used to evaluate the analytical procedure, where recovery around to 100% was obtained for all voltammetric techniques. Relative standard deviations were lower than 5.0% (N=5). The obtained t values evaluating all the three voltammetric methods were less than the tabulated ones, indicating that there are no evidences of systematic error. ©2005 Sociedade Brasileira de Química.
Keywords: Amoebiasis; Diloxanide furoate; Voltammetric determination